Transcript profiling for early stages during embryo development in Scots pine. Issue 1 (December 2016) - Merino, Irene; Abrahamsson, Malin; Sterck, Lieven; Craven-Bartle, Blanca; Canovas, Francisco; von Arnold, Sara
Abstract Background Characterization of the expression and function of genes regulating embryo development in conifers is interesting from an evolutionary point of view. However, our knowledge about the regulation of embryo development in conifers is limited. During early embryo development inPinus species the proembyo goes through a cleavage process, named cleavage polyembryony, giving rise to four embryos. One of these embryos develops to a dominant embryo, which will develop further into a mature, cotyledonary embryo, while the other embryos, the subordinate embryos, are degraded. The main goal of this study has been to identify processes that might be important for regulating the cleavage process and for the development of a dominant embryo. Results RNA samples from embryos and megagametophytes at four early developmental stages during seed development inPinus sylvestris were subjected to high-throughput sequencing. A total of 6.6 million raw reads was generated, resulting in 121, 938 transcripts, out of which 36.106 contained ORFs. 18, 638 transcripts were differentially expressed (DETs) in embryos and megagametophytes. GO enrichment analysis of transcripts up-regulated in embryos showed enrichment for different cellular processes, while those up-regulated in megagametophytes were enriched for accumulation of storage material and responses to stress. The highest number of DETs was detected during the initiation of the cleavage process. Transcripts related to embryogenic competence, cell wall modifications, cell division pattern, axis specification and response to hormones and stress were highly abundant and differentially expressed during early embryo development. The abundance of representative DETs was confirmed by qRT-PCR analyses. Conclusion Based on the processes identified in the GO enrichment analyses and the expression of the selected transcripts we suggest that (i) processes related to embryogenic competence and cell wall loosening are involved in activating the cleavage process; (ii) apical-basal polarization is strictly regulated in dominant embryos but not in the subordinate embryos; (iii) the transition from the morphogenic phase to the maturation phase is not completed in subordinate embryos. This is the first genome-wide transcript expression profiling of the earliest stages during embryo development in aPinus species. Our results can serve as a framework for future studies to reveal the functions of identified genes.